The Translation and Introduction of Augustine in the Republican Period - ZHOU, Weichi (Journal of Research for Christianity in China (JRCC), 2025)
Regarding the introduction and translation of Augustine in China, if we say that the transition between the Ming and Qing dynasties was “monopolized by a single family,” and, in the late-Qing period Protestant [translations] caught up, and with Catholicism “stood together as two peaks.” Then, in the Republican period, we can say that Catholicism, Protestantism, and humanist scholarship “stood on three feet.” The introduction to this article summarizes the general situation of the translation and discussion of Augustine in the Republican period, then separately introduces results of Catholic, Protestant, and humanist interpretations of Augustine.
Keywords: Augustine, Confessions, Frédéric-Vincent Lebbe, Giovanni Papini